Problematika Pendidikan Agama Islam dan Implikasinya terhadap Kehidupan Sehari-hari di Indonesia - Mumtahanah, Nurotun (JOIES (Journal of Islamic Education Studies), 2017)
Islamic education in Indonesia has been going on for a long time along with the entry of Islam in Indonesia. A number of literatures on the history of the development of Islam indicate that Islam entered and spread to Indonesia through Muslim traders both from Asia and the Middle East. Initially Islamic education was carried out informally between traders and or preachers with the surrounding community and then developed to a special place to study Islamic religion more deeply, orderly and orderly in delivering messages of Islamic teachings. In the process of Islamic education also encounters several problems that must be faced and resolved, Islamic education problems are the problems that occur in Islamic education.